Papers Presented at the Seventh Workshop on Empirical Studies of Programmers - ESP '97 1997
DOI: 10.1145/266399.266411
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of novice program comprehension in the imperative and object-oriented styles

Abstract: The objective of this study was to determine whether the mental representation of object-oriented programs differs from imperative programs for novice programmers. In our study novices who had little or no previous programming experience studied and answered questions about three imperative and three object-oriented programs. The questions targeted information categories making up the program model and the domain model representations of the programs. It was found that there was a sharp contrast between the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 17 publications
1
18
1
1
Order By: Relevance
“…Pennington (1987b) found this result for expert programmers comprehending small procedural programs, while Corritore and Wiedenbeck (1991) found a similar result for novices comprehending small procedural programs. Our prior experiment comparing procedural and OO program comprehension by novices also suggested a strong program model for procedural programs (Ramalingam & Wiedenbeck, 1997). However, in the current experiment control #ow questions were answered more poorly than in that experiment.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Pennington (1987b) found this result for expert programmers comprehending small procedural programs, while Corritore and Wiedenbeck (1991) found a similar result for novices comprehending small procedural programs. Our prior experiment comparing procedural and OO program comprehension by novices also suggested a strong program model for procedural programs (Ramalingam & Wiedenbeck, 1997). However, in the current experiment control #ow questions were answered more poorly than in that experiment.…”
Section: Discussioncontrasting
confidence: 53%
“…This experiment was designed to replicate a previous experiment (Ramalingam & Wiedenbeck, 1997). The results of the previous study indicated a strong functional component to novices' mental representations of OO programs.…”
Section: Research Questionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Three measures were conducted for student assessment: Computer Programming Self-Efficacy Scale [16], a time on task assessment, and a usability survey.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…There is as much literature discussing the value of teaching within one paradigm or another as literature discussing language choice (for example [7,8,9,10,12,19,24]). Certainly, if such an approach is necessary, then the results presented here must be qualified according to the instructor's choice of paradigm.…”
Section: Language Comparisonmentioning
confidence: 99%